Study of causes and possible solutions to the problem of specialist shortage in the Russian energy industry with the involvement of HR-branding - Bondarenko, V. A.; Popova, T. S.; Popov, A. A. (Глобальная ядерная безопасность, 2023)
This paper aims to identify the problems that mediate the shortage of specialists in the energy sector in Russia. The article analyzes the situation related to the insufficient popularity of engineering education among applicants, which leads to the risk of under-enrollment of students by universities within the budget enrollment control figures, which mediates difficulties in providing the quantitative parameter of the required specialists. Reduction of points for admission to technical profiles by universities leads to the attraction of applicants who do not demonstrate a conscious choice of future profession and, with a high probability, may refuse to work in their specialty, which is demonstrated by the presence in the energy sector of only 23% of specialists under 35 years of age, which is below the national average. As a result of the study it was determined that in the course of joint efforts of the state, universities and energy companies themselves to attract young people to engineering profession and work in the energy sector, the most active role should belong to employers. In this regard, the authors consider the expediency of using HR-branding in the format of expanding the target audience of potential employees of energy companies with the inclusion of preschoolers, schoolchildren and students to whom material and moral value proposition is made. Expanding the audience of the HR-brand of the company to preschoolers, schoolchildren and students, applying real moral and material motivators for them will contribute to the growth of popularity of this area of training and conscious choice of profession, which, in the long term, will solve the issue of the shortage of qualified personnel in the energy sector of Russia.